Peran Teknologi dan Sistem Informasi Akuntansi dalam Meningkatkan Kegiatan Operasional UMKM - Herman, Nur Melianda; Nirwana; Muhammad Alief Fahdal; Hasnawiyah Hasan (CV. AFDIFAL MAJU BERKAH, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in a country's economic growth. However, MSMEs often face challenges in managing their operations. This article aims to describe the role of technology and accounting information systems in improving the efficiency and effectiveness of MSME operations. This research uses the literature review method to analyze previously published articles, books, and other related sources. The results of this literature review reveal that technology and accounting information systems have become important tools in helping MSMEs overcome various obstacles in managing their business. Technologies such as accounting software, electronic payment systems and e-commerce platforms have changed the way MSMEs operate and communicate with their customers. This research also highlights the benefits provided by technology in optimizing inventory management, financial monitoring, and data analysis for better decision-making.